2005
DOI: 10.1007/s11249-005-7789-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Contact on the Abrasiveness of a Thin Boron Carbide Coating

Abstract: Boron carbide (B 4 C) has been studied under dry sliding conditions for use as a potential finite-life run-in coating. Such a coating has been found to polish its mating surface during dry sliding wear, thereby providing fatigue resistance to the coated part. Employing such run-in coatings requires a complete understanding of the changes that occur in the coating abrasiveness during the polishing process. Therefore, a thorough understanding of the changes in the contact conditions of such a system needs to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 11 publications
5
10
0
Order By: Relevance
“…The average coating abrasiveness versus the number of ball-on-disc cycles is plotted on a log-log scale in figure 1 for both the lubricated and dry sliding conditions. In agreement with previous findings of the B 4 C coating under dry sliding conditions [3][4][5][6][7][8], the average coating abrasiveness decreased with increasing sliding distance following a power law scaling relationship for both the lubricated and dry cases. Because of the linear relationships present in the coating abrasiveness results of figure 1, it can be shown [9] that the instantaneous coating abrasiveness A n at any given cycle n is given by…”
Section: Coating Abrasiveness Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The average coating abrasiveness versus the number of ball-on-disc cycles is plotted on a log-log scale in figure 1 for both the lubricated and dry sliding conditions. In agreement with previous findings of the B 4 C coating under dry sliding conditions [3][4][5][6][7][8], the average coating abrasiveness decreased with increasing sliding distance following a power law scaling relationship for both the lubricated and dry cases. Because of the linear relationships present in the coating abrasiveness results of figure 1, it can be shown [9] that the instantaneous coating abrasiveness A n at any given cycle n is given by…”
Section: Coating Abrasiveness Resultssupporting
confidence: 92%
“…The abrasiveness of a thin B 4 C coating sliding against 52100 bearing steel under dry conditions has extensively been studied by Harris et al [3] and Siniawski et al [4][5][6][7][8] using a ball-on-disc machine. From these studies, it was observed that the B 4 C coating polished the steel ball counterpart relatively quickly, in approximately 30 cycles of abrasive wear at a sliding velocity of 10 cm/s under a 100 g load.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations